High performance low cost ti-fe-o-n alloy and method of making
Patent Information
- Application Number
- CN202611276058.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-21
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]然而,现有的主流钛合金熔炼技术--真空自耗电弧熔炼和冷床炉熔炼(电子束/等离子束),均存在制约低成本与高性能兼得的技术缺陷
(1)本发明以低成本的Fe替代昂贵的V作为β稳定元素,同时将常规认知中有害的间隙元素O和N转化为有益的α稳定元素加以利用,有效替代了Al元素,大幅降低了合金的原料成本,同时突破了传统钛合金对Fe、O、N含量的严格限制,拓宽了高性能低成本Ti-Fe-O-N合金的成分设计空间。
Smart Images

Figure CN122918388A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of titanium alloy material design and preparation technology, specifically relating to a high-performance, low-cost Ti-Fe-ON alloy and its preparation method. Background Technology
[0002] Titanium alloys, with their core advantages such as low density, high specific strength, excellent corrosion resistance, good high-temperature performance, and good biocompatibility, have become indispensable key structural materials in modern industrial systems. Their applications have expanded from traditional high-end fields such as aerospace to multiple industries including marine engineering, biomedicine, automotive manufacturing, and national defense, forming a diversified application pattern. However, the high production cost and significant processing difficulty of titanium alloys severely restrict their large-scale promotion. Furthermore, as the application scenarios and working conditions of titanium alloys become increasingly complex and extreme, more stringent requirements are being placed on their mechanical properties, corrosion resistance, and environmental adaptability.
[0003] At the alloying design level, the alloying elements in titanium alloys are mainly divided into α-stabilizing elements (such as Al, O and N) and β-stabilizing elements (such as V, Mo, Ni, Fe, Cr, Mn and Nb). In order to reduce the cost of raw materials, cheaper alloying elements are usually used to replace more expensive alloying elements.
[0004] In the existing commercial titanium alloy system, Ti-6Al-4V alloy has a market share of over 60%, maintaining its dominant position due to its stable room-temperature mechanical properties and corrosion resistance. However, this alloy contains the expensive β-stabilizing element V (vanadium), whose market price reaches hundreds of thousands of yuan per ton, significantly increasing the cost of raw materials. In contrast, Fe (iron), also a β-stabilizing element, has a market price of only several thousand yuan per ton. Therefore, replacing the precious metal V with the low-cost element Fe, and replacing Al (aluminum) with the α-stabilizing elements O (oxygen) and N (nitrogen), is considered one of the most promising alloying pathways to reduce the cost of titanium alloy raw materials.
[0005] However, existing mainstream titanium alloy melting technologies—vacuum arc melting and cold hearth furnace melting (electron beam / plasma beam)—both have technical drawbacks that limit the achievement of both low cost and high performance. Specifically, vacuum arc melting easily leads to macroscopic and microscopic segregation in the alloy, resulting in poor alloy composition uniformity and structural defects; while cold hearth furnace melting has high equipment investment and operating costs, hindering the low-cost preparation of titanium alloys. In particular, for Fe-containing titanium alloys, the above melting methods all use water-cooled copper crucibles without electromagnetic stirring, which easily induces Fe element segregation, forming harmful β spots that seriously affect alloy properties; for the addition of N element, existing processes mostly use nitrides for alloying, but nitrides are difficult to dissolve and diffuse, easily causing uneven distribution of N element, thus affecting alloy properties. In addition, some studies have attempted to introduce nitrogen by directly introducing nitrogen gas during the smelting process, but this method also has many problems: the solubility and diffusion coefficient of nitrogen in titanium melt are extremely low, the absorption rate is unstable, and it is difficult to accurately control the nitrogen content; the introduced nitrogen gas is prone to forming refractory solid films such as TiN on the surface of the melt, which hinders the further dissolution of nitrogen and may remain in the form of inclusions, reducing the plasticity of the material.
[0006] In conventional technical understanding, oxygen (O) and nitrogen (N) are considered harmful interstitial elements in titanium alloys, and their content must be strictly controlled. Although iron (Fe) can reduce raw material costs, its addition is usually limited to a low level (generally below 5%), otherwise it will deteriorate processing performance. Therefore, in existing technologies, O and N are generally not considered beneficial additive elements, and the addition of Fe is also strictly limited. This greatly restricts the composition design space and performance improvement potential of low-cost titanium alloys.
[0007] Therefore, there is an urgent need to develop a high-performance, low-cost Ti-Fe-ON alloy and its preparation method to solve the many problems existing in the above-mentioned technologies and break through the technical bottleneck of large-scale application of titanium alloys. Summary of the Invention
[0008] To address the problems existing in the prior art, this invention provides a high-performance, low-cost Ti-Fe-ON alloy. The mass percentage content of each element in the Ti-Fe-ON alloy is as follows: 5wt% < Fe ≤ 8wt%, 0.2wt% ≤ O + N ≤ 0.5wt%, the mass ratio of N to O is 1:4-6, and the balance is Ti. The Fe content is negatively correlated with the sum of the N + O content. Within the range of the sum of the Fe content and the N + O content, for every 1wt% increase in the Fe addition, the N + O addition decreases by 0.08-0.1wt%.
[0009] This invention also provides a method for preparing a high-performance, low-cost Ti-Fe-ON alloy, the method comprising the following steps in sequence: Step 1: Prepare a crucible for Ba2(YNb)O4NF material according to the preset material ratio and process system; Step 2: Place the crucible in a vacuum induction melting furnace, and simultaneously put metallic titanium and metallic iron into the crucible; Step 3: Turn off the vacuum induction melting furnace and evacuate the furnace cavity to the preset vacuum level. While maintaining the preset vacuum level, gradually increase the power to induction heat the titanium and iron metals. Step 4: During the heating process of titanium and iron, high-purity argon gas is introduced for protection. After the titanium and iron turn red and reach the preset temperature, the temperature is held for a preset time, and then the temperature is continued to rise until the metal is completely melted. After the metal is completely melted, it is refined according to the preset refining temperature and refining time. After refining, the alloy melt is cast into an ingot to obtain a high-performance, low-cost Ti-Fe-ON alloy.
[0010] Preferably, in step one, the raw materials for preparing the Ba2(YNb)O4NF material crucible include barium carbonate, barium fluoride, yttrium oxide, niobium oxide, and ammonia. The mass ratio of barium carbonate, barium fluoride, yttrium oxide, and niobium oxide is 1:1.2-1.6:0.5:0.5, and the mass ratio of the sum of the masses of barium carbonate, barium fluoride, yttrium oxide, and niobium oxide to the mass of ammonia is 1:0.2-1.3. The particle size of barium carbonate, barium fluoride, yttrium oxide, and niobium oxide is controlled within the range of 50-100 μm.
[0011] Preferably, in any of the above schemes, step one of the preparation method of the Ba2(YNb)O4NF material includes the following steps in sequence: Step 1.1: Place barium carbonate, barium fluoride, yttrium oxide and niobium oxide into a mixer and mix them evenly at room temperature. The mixing speed is 500-800 rpm and the mixing time is 30-60 min to obtain a dry powder mixture. Step 1.2: Place the dry powder mixture into a ceramic container, then place the ceramic container in a sintering furnace and perform the first sintering treatment under atmospheric atmosphere according to the following sintering regime: raise the temperature from room temperature to 200℃ at a heating rate of 0.8-1.5℃ / min, hold for 1-1.5h, continue to raise the temperature to 800℃ at a heating rate of 1.5-2℃ / min, hold for 2-4h, continue to raise the temperature to 1300℃ at a heating rate of 3-4℃ / min, hold for 10-20h, and cool to room temperature with the furnace to obtain Ba2YNbO. 5.5 F material; Step 1.3: Add Ba2YNbO 5.5 Material F was placed in a ball mill jar, along with deionized water and zirconia grinding beads. The first ball milling treatment was performed at room temperature, including the following main ball milling process parameters: Ba2YNbO5.5 The mass ratio of F material, zirconia grinding beads, and deionized water is 1:1.8-2.2:0.6-1. The diameter of the zirconia grinding beads is 6-8 mm, the grinding speed is 180-220 rpm, and the grinding time is 6-12 h. Step 1.4: The Ba2YNbO after the first ball milling treatment... 5.5 Material F is placed in an oven for drying at a temperature of 120-150℃ for 4-6 hours. During this drying process, Ba₂YNbO₂... 5.5 The particle size of material F is controlled within the range of 30-40 μm; Step 1.5: Dry the Ba2YNbO 5.5 Material F is placed in a ceramic container, and then the ceramic container is placed in a sintering furnace for a second sintering treatment according to the following sintering regime: ammonia gas is introduced at a flow rate of 20-30 mL / min, the temperature is raised from room temperature to 1000℃ at a heating rate of 1.2-1.8℃ / min, held at the temperature for 40-50 h, and then cooled to room temperature with the furnace to obtain Ba2(YNb)O4NF material. Step 1.6: Place the Ba2(YNb)O4NF material into a ball mill jar, and add deionized water and zirconia grinding beads. Perform a second ball milling treatment at room temperature, including the following main ball milling process parameters: the mass ratio of Ba2(YNb)O4NF material, zirconia grinding beads, and deionized water is 1:1.2-1.5:0.6-1, the diameter of the zirconia grinding beads is 3-5mm, the ball milling speed is 180-220rpm, and the ball milling time is 6-12h. Step 1.7: Place the Ba2(YNb)O4NF material after the second ball milling treatment into an oven for drying. The drying temperature is 120-150℃ and the drying time is 4-6h. At this time, the particle size of the Ba2(YNb)O4NF material is controlled within the range of 10-20μm.
[0012] In any of the above schemes, it is preferred that, in step one, the preparation method of the Ba2(YNb)O4NF material crucible includes the following steps in sequence: First, pour the dried Ba2(YNb)O4NF material into a U-shaped crucible mold; Then, the crucible blank is formed by pressing at room temperature using a cold isostatic pressing equipment with a pressing pressure of 100-150MPa and a holding time of 5-10min. Finally, the crucible blank is placed in a sintering furnace and sintered under a nitrogen atmosphere according to the following sintering regime: the temperature is increased from room temperature to 300℃ at a heating rate of 1-3℃ / min, held for 2-4 hours, then increased to 1000℃ at a heating rate of 3-5℃ / min, held for 5-6 hours, then increased to 1580-1650℃ at a heating rate of 1-3℃ / min, held for 8-12 hours, and then cooled to room temperature with the furnace to obtain the Ba2(YNb)O4NF material crucible.
[0013] In any of the above schemes, it is preferred that, in step two, the titanium metal is added in any of the following forms: sponge titanium, titanium metal block, or titanium powder, and the iron metal is added in any of the following forms: iron powder, iron granules, or iron block.
[0014] In any of the above schemes, it is preferred that, in step three, the furnace cavity is evacuated to 1×10⁻⁶. -3 ~1×10 -2 Pa.
[0015] In any of the above schemes, it is preferred that in step four, the titanium and iron metals glow red and reach a preset temperature of 600-1200℃, and the holding time is 1-10 minutes.
[0016] In any of the above schemes, it is preferred that in step four, the temperature is further increased until the metal is completely melted, and the melting temperature is 1630-1680℃.
[0017] In any of the above schemes, it is preferred that in step four, the refining temperature is 1700-1850℃ and the refining time is 1-10min; the casting mold includes any one of metal shell, graphite shell and ceramic shell.
[0018] The vacuum induction melting furnace, mixer, sintering furnace, ball mill (including ball mill jar), drying oven, and cold isostatic pressing equipment used in this invention can be selected from existing equipment according to actual usage, without special requirements on equipment model and structure. After the Ti-Fe-ON alloy is refined, the alloy liquid is taken out from the vacuum induction melting furnace for pouring to obtain castings. The pouring equipment and pouring process used can adopt traditional techniques.
[0019] The Ti-Fe-ON alloy prepared by this invention does not belong to any grade of titanium alloy, but is an independent non-standard alloy. It is prepared by crucible vacuum induction melting technology, directly adding metallic titanium and metallic iron, with O and N introduced through a crucible made of Ba2(YNb)O4NF material. In the prior art, O and N are introduced by adding nitrides and oxides, or by introducing N through nitrogen gas.
[0020] Existing technologies that directly add nitrides, oxides, or introduce O and N through nitrogen gas suffer from drawbacks such as difficulty in precisely controlling composition, easy introduction of impurities, and conflict with the deoxidation and element volatilization characteristics of vacuum melting. This invention innovatively introduces O and N into the alloy melt precisely, uniformly, and cleanly through crucible material, effectively avoiding the shortcomings of existing technologies and providing a new technical route for preparing high-performance, low-cost Ti-Fe-ON non-standard alloys.
[0021] This invention innovatively develops Ba2(YNb)O4NF material, which is prepared from barium carbonate (BaCO3), barium fluoride (BaF2), yttrium oxide (Y2O3), niobium oxide (Nb2O5), and ammonia (NH3). The preparation process of Ba2(YNb)O4NF material includes two sintering treatments, each involving a different chemical reaction: The following chemical reactions occur during the first sintering process: The following chemical reactions occur during the second sintering process: The present invention relates to a high-performance, low-cost Ti-Fe-ON alloy and its preparation method, which has the following beneficial effects: (1) This invention uses low-cost Fe to replace expensive V as the β-stabilizing element, and at the same time transforms the commonly recognized harmful interstitial elements O and N into beneficial α-stabilizing elements for use, effectively replacing Al elements and significantly reducing the raw material cost of the alloy. It also breaks through the strict restrictions on Fe, O and N content in traditional titanium alloys, and broadens the composition design space of high-performance low-cost Ti-Fe-ON alloys.
[0022] (2) Compared with existing technologies that introduce O and N by directly adding nitrides, oxides, or by introducing nitrogen gas, this invention innovatively prepares a Ba2(YNb)O4NF material crucible. During the melting process, the crucible contacts the alloy melt, uniformly and stably introducing O and N into the alloy melt. This method effectively avoids the problems of difficult dissolution and diffusion of nitrides and uneven distribution of N element in existing technologies. At the same time, it overcomes the defects of the nitrogen gas method, such as unstable absorption rate due to low nitrogen solubility and diffusion coefficient, easy formation of TiN refractory film and inclusion residue, thereby ensuring high uniformity and high purity of Ti-Fe-ON alloy composition.
[0023] (3) The present invention adopts crucible-type vacuum induction melting technology. Compared with the vacuum self-consuming electric arc melting and cold hearth furnace melting in the prior art, it has electromagnetic stirring effect, which can effectively suppress the segregation of Fe element and avoid the formation of harmful β spots, thereby obtaining Ti-Fe-ON alloy castings with uniform structure and stable performance.
[0024] (4) The Ti-Fe-ON alloy prepared by this invention, while ensuring low cost, possesses high strength, good plasticity, and excellent corrosion resistance. It can meet the application needs of titanium alloys in complex and extreme chemical conditions in multiple fields such as aerospace, marine engineering, biomedicine, and automobile manufacturing, breaking through the technical bottleneck of large-scale application of titanium alloys and having significant economic and social benefits. (5) This invention breaks through traditional understanding by transforming O and N elements, which are conventionally considered harmful, into beneficial strengthening elements. Through the synergistic design of alloy composition and preparation process, it achieves the addition of high-content Fe elements without impairing processing performance, thereby obtaining excellent comprehensive mechanical properties, corrosion resistance, and formability while ensuring low cost. Based on the material system and preparation process of this invention, high-strength, low-cost Ti-Fe-ON alloys can be prepared and effectively replaced by commercial Ti-6Al-4V alloys, providing a new technical path for solving the technical bottleneck of large-scale application of titanium alloys. Attached Figure Description
[0025] Figure 1 The image shows the macroscopic morphology of a Ti-Fe-ON alloy ingot prepared according to a preferred embodiment of the high-performance, low-cost Ti-Fe-ON alloy and its preparation method of the present invention. Figure 2 for Figure 1 Backscattered electron morphology of the Ti-Fe-ON alloy ingot prepared in the example shown; Figure 3 for Figure 1 Elemental distribution diagram of Ti-Fe-ON alloy ingots prepared in the illustrated embodiment; Figure 4 A comparison of the corrosion resistance of Ti-Fe-ON alloy ingots prepared for the four examples with that of Ti-6Al-4V alloy ingots of the prior art. Detailed Implementation
[0026] To further understand the invention, the following detailed description of the invention will be provided in conjunction with specific embodiments.
[0027] Example 1: According to a preferred embodiment of the high-performance, low-cost Ti-Fe-ON alloy of the present invention, the mass percentage content of each element in the Ti-Fe-ON alloy is as follows: 5wt% < Fe ≤ 8wt%, 0.2wt% ≤ O + N ≤ 0.5wt%, the mass ratio of N to O is 1:4-6, and the balance is Ti; the Fe content is negatively correlated with the sum of N + O content. Within the range of the sum of Fe content and N + O content, when the amount of Fe added increases by 1wt%, the amount of N + O added decreases by 0.08-0.1wt%.
[0028] In this embodiment, Fe is added at the minimum amount, and O+N is added at the maximum amount. The Fe content is 5.001 wt% (higher than 5 wt%, but infinitely close to 5 wt%), the O+N content is 0.5 wt%, the mass ratio of N to O is 1:5, and the balance is Ti.
[0029] This embodiment also provides a method for preparing a high-performance, low-cost Ti-Fe-ON alloy, the preparation method comprising the following steps in sequence: Step 1: Prepare a crucible for Ba2(YNb)O4NF material according to the preset material ratio and process system; Step 2: Place the crucible in a vacuum induction melting furnace, and simultaneously put metallic titanium and metallic iron into the crucible; Step 3: Turn off the vacuum induction melting furnace and evacuate the furnace cavity to the preset vacuum level. While maintaining the preset vacuum level, gradually increase the power to induction heat the titanium and iron metals. Step 4: During the heating process of titanium and iron, high-purity argon gas is introduced for protection. After the titanium and iron turn red and reach the preset temperature, the temperature is held for a preset time, and then the temperature is continued to rise until the metal is completely melted. After the metal is completely melted, it is refined according to the preset refining temperature and refining time. After refining, the alloy melt is cast into an ingot to obtain a high-performance, low-cost Ti-Fe-ON alloy.
[0030] In step one, the raw materials for preparing the Ba2(YNb)O4NF material crucible include barium carbonate, barium fluoride, yttrium oxide, niobium oxide, and ammonia. The mass ratio of barium carbonate, barium fluoride, yttrium oxide, and niobium oxide is 1:1.4:0.5:0.5, and the mass ratio of the sum of the masses of barium carbonate, barium fluoride, yttrium oxide, and niobium oxide to the mass of ammonia is 1:0.8. The particle size of barium carbonate, barium fluoride, yttrium oxide, and niobium oxide is controlled within the range of 50-100 μm.
[0031] The preparation method of the Ba2(YNb)O4NF material includes the following steps in sequence: Step 1.1: Place barium carbonate, barium fluoride, yttrium oxide and niobium oxide into a mixer and mix them evenly at room temperature. The mixing speed is 650 rpm and the mixing time is 45 min to obtain a dry powder mixture. Step 1.2: Place the dry powder mixture into a ceramic container, then place the ceramic container in a sintering furnace and perform the first sintering treatment under atmospheric atmosphere according to the following sintering regime: raise the temperature from room temperature to 200℃ at a heating rate of 1.2℃ / min, hold for 1.2h, continue to raise the temperature to 800℃ at a heating rate of 1.8℃ / min, hold for 3h, continue to raise the temperature to 1300℃ at a heating rate of 3.5℃ / min, hold for 15h, and then cool to room temperature in the furnace to obtain Ba2YNbO. 5.5 F material; Step 1.3: Add Ba2YNbO 5.5 Material F was placed in a ball mill jar, along with deionized water and zirconia grinding beads. The first ball milling treatment was performed at room temperature, including the following main ball milling process parameters: Ba2YNbO 5.5 The mass ratio of material F, zirconia grinding beads, and deionized water is 1:2:0.8. The diameter of the zirconia grinding beads is 7 mm, the grinding speed is 200 rpm, and the grinding time is 9 hours. Step 1.4: The Ba2YNbO after the first ball milling treatment... 5.5 Material F was placed in an oven for drying at 135℃ for 5 hours. At this time, Ba₂YNbO₂... 5.5 The particle size of material F is controlled within the range of 30-40 μm; Step 1.5: Dry the Ba2YNbO 5.5 Material F was placed in a ceramic container, and then the ceramic container was placed in a sintering furnace. A second sintering treatment was carried out according to the following sintering regime: ammonia gas was introduced at a flow rate of 25 mL / min, the temperature was raised from room temperature to 1000℃ at a heating rate of 1.5℃ / min, held at the temperature for 45 h, and cooled to room temperature with the furnace to obtain Ba2(YNb)O4NF material. Step 1.6: Place the Ba2(YNb)O4NF material into a ball mill jar, and add deionized water and zirconia grinding beads. Perform a second ball milling treatment at room temperature, including the following main ball milling process parameters: the mass ratio of Ba2(YNb)O4NF material, zirconia grinding beads, and deionized water is 1:1.3:0.8, the diameter of the zirconia grinding beads is 4mm, the ball milling speed is 200rpm, and the ball milling time is 9h. Step 1.7: Place the Ba2(YNb)O4NF material after the second ball milling treatment into an oven for drying. The drying temperature is 135℃ and the drying time is 5h. At this time, the particle size of the Ba2(YNb)O4NF material is controlled within the range of 10-20μm.
[0032] The preparation method of the Ba2(YNb)O4NF material crucible includes the following steps in sequence: First, the dried Ba2(YNb)O4NF material is poured into a U-shaped crucible mold; then, it is pressed at room temperature using a cold isostatic pressing equipment at a pressing pressure of 125 MPa and a holding time of 7.5 min to obtain a crucible blank; finally, the crucible blank is placed in a sintering furnace and sintered under a nitrogen atmosphere according to the following sintering regime: the temperature is increased from room temperature to 300℃ at a heating rate of 2℃ / min, held for 3 h, then increased to 1000℃ at a heating rate of 4℃ / min, held for 5.5 h, then increased to 1615℃ at a heating rate of 2℃ / min, held for 10 h, and then cooled to room temperature with the furnace to obtain the Ba2(YNb)O4NF material crucible.
[0033] In step two, the titanium metal is added in any of the following forms: sponge titanium, titanium metal blocks, or titanium powder; and the iron metal is added in any of the following forms: iron powder, iron granules, or iron blocks.
[0034] In step three, the furnace cavity is evacuated to a vacuum level of 1×10⁻⁶. -3 ~1×10 -2 Pa.
[0035] In step four, the titanium and iron metals glow red and reach a preset temperature of 900°C, with a holding time of 5.5 minutes; the temperature continues to rise until the metals are completely melted, with a melting temperature of 1655°C; the refining temperature is 1775°C, and the refining time is 5.5 minutes; the casting mold includes any one of a metal shell, a graphite shell, and a ceramic shell, and in this embodiment, a cylindrical graphite shell is used.
[0036] The Ti-Fe-ON alloy prepared in this embodiment does not belong to any grade of titanium alloy, but is an independent non-standard alloy. It is prepared by crucible vacuum induction melting technology by adding metallic titanium and metallic iron directly. The O and N are introduced through a crucible made of Ba2(YNb)O4NF material.
[0037] This embodiment innovatively develops Ba2(YNb)O4NF material, which is prepared from barium carbonate (BaCO3), barium fluoride (BaF2), yttrium oxide (Y2O3), niobium oxide (Nb2O5), and ammonia (NH3). The preparation process of Ba2(YNb)O4NF material includes two sintering processes, each involving a different chemical reaction: The following chemical reactions occur during the first sintering process: The following chemical reactions occur during the second sintering process: This embodiment has the following beneficial effects: (1) It uses low-cost Fe to replace expensive V as the β-stabilizing element, and at the same time transforms the commonly recognized harmful interstitial elements O and N into beneficial α-stabilizing elements for utilization, which greatly reduces the raw material cost of the alloy and breaks through the strict restrictions on the Fe, O, and N content of traditional titanium alloys. (2) It innovatively prepares a Ba2(YNb)O4NF material crucible, which introduces O and N uniformly and stably into the alloy melt through contact between the crucible and the alloy melt during the melting process. (3) It adopts crucible-type vacuum induction melting technology, which has an electromagnetic stirring effect compared with the existing vacuum self-consuming arc melting and cold hearth furnace melting, which can effectively suppress the segregation of Fe element and avoid the formation of harmful β spots, thereby obtaining Ti-Fe-ON alloy castings with uniform structure and stable performance. (4) The prepared Ti-Fe-ON alloy has high strength, good plasticity and excellent corrosion resistance while ensuring low cost. (5) Through the synergistic design of alloy composition and preparation process, the addition of high Fe content can be achieved without impairing processing performance, thereby obtaining excellent comprehensive mechanical properties, corrosion resistance and formability while ensuring low cost, and realizing an effective replacement for commercial Ti-6Al-4V alloy.
[0038] Example 2: According to another preferred embodiment of the high-performance, low-cost Ti-Fe-ON alloy and its preparation method of the present invention, the material selection and proportioning, preparation process, technical principle, and beneficial effects are basically the same as those in Embodiment 1, except that: The mass percentage of each element in the Ti-Fe-ON alloy is as follows: Fe content is 6wt%, O+N content is 0.42wt%, N to O mass ratio is 1:4, and the balance is Ti. The Fe content is negatively correlated with the sum of N+O content. Within the range of Fe content and the sum of N+O content, for every 1wt% increase in Fe addition, the N+O addition decreases by 0.08wt% accordingly, ensuring that it is within the range of 0.08-0.1wt%.
[0039] In step one, the raw materials for preparing the Ba2(YNb)O4NF material crucible have a mass ratio of barium carbonate, barium fluoride, yttrium oxide, and niobium oxide of 1:1.2:0.5:0.5, and the sum of the masses of the four powder substances is in a mass ratio of 1:0.2 with the mass of ammonia.
[0040] The preparation method of the Ba2(YNb)O4NF material includes the following steps in sequence: Step 1.1: Place barium carbonate, barium fluoride, yttrium oxide and niobium oxide into a mixer and mix them evenly at room temperature. The mixing speed is 500 rpm and the mixing time is 60 min to obtain a dry powder mixture. Step 1.2: Place the dry powder mixture into a crucible container in a sintering furnace and perform the first sintering treatment under atmospheric atmosphere according to the following sintering regime: raise the temperature from room temperature to 200℃ at a heating rate of 0.8℃ / min, hold for 1 hour, continue to raise the temperature to 800℃ at a heating rate of 1.5℃ / min, hold for 2 hours, continue to raise the temperature to 1300℃ at a heating rate of 3℃ / min, hold for 10 hours, and then cool to room temperature with the furnace to obtain Ba2YNbO. 5.5 F material; Step 1.3: Add Ba2YNbO 5.5 Material F was placed in a ball mill jar, along with deionized water and zirconia grinding beads. The first ball milling treatment was performed at room temperature, including the following main ball milling process parameters: Ba2YNbO 5.5 The mass ratio of material F, zirconia grinding beads, and deionized water is 1:1.8:0.6. The diameter of the zirconia grinding beads is 6mm, the grinding speed is 180rpm, and the grinding time is 12h. Step 1.4: The Ba2YNbO after the first ball milling treatment... 5.5 Material F is placed in an oven for drying at 120℃ for 6 hours. Step 1.5: Dry the Ba2YNbO 5.5 Material F was placed in a crucible container in a sintering furnace and subjected to a second sintering process according to the following sintering regime: ammonia gas was introduced at a flow rate of 20 mL / min, the temperature was increased from room temperature to 1000℃ at a heating rate of 1.2℃ / min, held at the temperature for 40 h, and then cooled to room temperature with the furnace to obtain Ba2(YNb)O4NF material. Step 1.6: Place the Ba2(YNb)O4NF material into a ball mill jar, and add deionized water and zirconia grinding beads. Perform a second ball milling treatment at room temperature, including the following main ball milling process parameters: mass ratio of Ba2(YNb)O4NF material, zirconia grinding beads, and deionized water 1:1.2:0.6, diameter of zirconia grinding beads 3mm, ball milling speed 180rpm, and ball milling time 12h; Step 1.7: Place the Ba2(YNb)O4NF material after the second ball milling treatment into an oven for drying at 120℃ for 6 hours.
[0041] The preparation method of the Ba2(YNb)O4NF material crucible includes the following main process parameters: The crucible blank is obtained by pressing at room temperature using a cold isostatic pressing equipment at a pressing pressure of 100 MPa and a holding time of 10 min; the crucible blank is then placed in a sintering furnace and sintered under a nitrogen atmosphere according to the following sintering regime: the temperature is increased from room temperature to 300℃ at a heating rate of 1℃ / min, held for 2 h, then increased to 1000℃ at a heating rate of 3℃ / min, held for 5 h, then increased to 1580℃ at a heating rate of 1℃ / min, held for 8 h, and finally cooled to room temperature in the furnace to obtain the Ba2(YNb)O4NF material crucible.
[0042] In step four, the titanium and iron metals glow red and reach a preset temperature of 600°C, with a holding time of 10 minutes; the temperature continues to rise until the metals are completely melted, with a melting temperature of 1630°C; the refining temperature is 1700°C, and the refining time is 10 minutes.
[0043] Example 3: According to another preferred embodiment of the high-performance, low-cost Ti-Fe-ON alloy and its preparation method of the present invention, the material selection and proportioning, preparation process, technical principle, and beneficial effects are basically the same as those in Embodiment 1, except that: The mass percentage of each element in the Ti-Fe-ON alloy is as follows: Fe content is 7wt%, O+N content is 0.32wt%, the mass ratio of N to O is 1:6, and the balance is Ti. The Fe content is negatively correlated with the sum of N+O content. Within the range of the sum of Fe content and N+O content, for every 1wt% increase in Fe addition, the N+O addition decreases by 0.1wt% accordingly, ensuring that it is within the range of 0.08-0.1wt%.
[0044] In step one, the raw materials for preparing the Ba2(YNb)O4NF material crucible have a mass ratio of barium carbonate, barium fluoride, yttrium oxide, and niobium oxide of 1:1.6:0.5:0.5, and the sum of the masses of the four powder substances is in a mass ratio of 1:1.3 with the mass of ammonia.
[0045] The preparation method of the Ba2(YNb)O4NF material includes the following steps in sequence: Step 1.1: Place barium carbonate, barium fluoride, yttrium oxide and niobium oxide into a mixer and mix them evenly at room temperature. The mixing speed is 800 rpm and the mixing time is 30 min to obtain a dry powder mixture. Step 1.2: Place the dry powder mixture into a crucible container in a sintering furnace and perform the first sintering treatment under atmospheric atmosphere according to the following sintering regime: heat from room temperature to 200℃ at a heating rate of 1.5℃ / min, hold for 1.5h, continue heating to 800℃ at a heating rate of 2℃ / min, hold for 4h, continue heating to 1300℃ at a heating rate of 4℃ / min, hold for 20h, and then cool to room temperature with the furnace to obtain Ba2YNbO. 5.5 F material; Step 1.3: Add Ba2YNbO 5.5 Material F was placed in a ball mill jar, along with deionized water and zirconia grinding beads. The first ball milling treatment was performed at room temperature, including the following main ball milling process parameters: Ba2YNbO 5.5 The mass ratio of material F, zirconia grinding beads, and deionized water is 1:2.2:1. The diameter of the zirconia grinding beads is 8mm, the grinding speed is 220rpm, and the grinding time is 6h. Step 1.4: The Ba2YNbO after the first ball milling treatment... 5.5 Material F is placed in an oven for drying at 150℃ for 4 hours. Step 1.5: Dry the Ba2YNbO 5.5 Material F was placed in a crucible container in a sintering furnace and subjected to a second sintering process according to the following sintering regime: ammonia gas was introduced at a flow rate of 30 mL / min, the temperature was increased from room temperature to 1000℃ at a heating rate of 1.8℃ / min, held at that temperature for 50 h, and then cooled to room temperature with the furnace to obtain Ba2(YNb)O4NF material. Step 1.6: Place the Ba2(YNb)O4NF material into a ball mill jar, and add deionized water and zirconia grinding beads. Perform a second ball milling treatment at room temperature, including the following main ball milling process parameters: mass ratio of Ba2(YNb)O4NF material, zirconia grinding beads, and deionized water 1:1.5:1, diameter of zirconia grinding beads 5mm, ball milling speed 220rpm, and ball milling time 6h; Step 1.7: Place the Ba2(YNb)O4NF material after the second ball milling treatment into an oven for drying at 150℃ for 4 hours.
[0046] The preparation method of the Ba2(YNb)O4NF material crucible includes the following main process parameters: The crucible blank is obtained by pressing at room temperature using a cold isostatic pressing equipment at a pressing pressure of 150 MPa and a holding time of 5 min; the crucible blank is then placed in a sintering furnace and sintered under a nitrogen atmosphere according to the following sintering regime: the temperature is increased from room temperature to 300℃ at a heating rate of 3℃ / min, held for 4 h, then increased to 1000℃ at a heating rate of 5℃ / min, held for 6 h, then increased to 1650℃ at a heating rate of 3℃ / min, held for 12 h, and finally cooled to room temperature in the furnace to obtain the Ba2(YNb)O4NF material crucible.
[0047] In step four, the titanium and iron metals glow red and reach a preset temperature of 1200℃, with a holding time of 1 minute; the temperature continues to rise until the metals are completely melted, with a melting temperature of 1680℃; the refining temperature is 1850℃, and the refining time is 1 minute.
[0048] Example 4: According to another preferred embodiment of the high-performance, low-cost Ti-Fe-ON alloy and its preparation method of the present invention, the material selection and proportioning, preparation process, technical principle, and beneficial effects are basically the same as those in Embodiment 1, except that: The mass percentage of each element in the Ti-Fe-ON alloy is as follows: Fe content is 8 wt%, O+N content is 0.22 wt%, the mass ratio of N to O is 1:5, and the balance is Ti. The Fe content is negatively correlated with the sum of N+O content. Within the range of the sum of Fe content and N+O content, for every 1 wt% increase in Fe addition, the N+O addition decreases by 0.1 wt% accordingly, ensuring that it is within the range of 0.08-0.1 wt%.
[0049] In step one, the raw materials for preparing the Ba2(YNb)O4NF material crucible have a mass ratio of barium carbonate, barium fluoride, yttrium oxide, and niobium oxide of 1:1.4:0.5:0.5, and the sum of the masses of the four powder substances is in a mass ratio of 1:0.8 with that of ammonia.
[0050] The preparation method of the Ba2(YNb)O4NF material includes the following steps in sequence: Step 1.1: Place barium carbonate, barium fluoride, yttrium oxide and niobium oxide into a mixer and mix them evenly at room temperature. The mixing speed is 650 rpm and the mixing time is 45 min to obtain a dry powder mixture. Step 1.2: Place the dry powder mixture into a crucible container in a sintering furnace and perform the first sintering treatment under atmospheric atmosphere according to the following sintering regime: raise the temperature from room temperature to 200℃ at a heating rate of 1.2℃ / min, hold for 1.2h, continue to raise the temperature to 800℃ at a heating rate of 1.8℃ / min, hold for 3h, continue to raise the temperature to 1300℃ at a heating rate of 3.5℃ / min, hold for 15h, and then cool to room temperature with the furnace to obtain Ba2YNbO. 5.5 F material; Step 1.3: Add Ba2YNbO 5.5 Material F was placed in a ball mill jar, along with deionized water and zirconia grinding beads. The first ball milling treatment was performed at room temperature, including the following main ball milling process parameters: Ba2YNbO 5.5 The mass ratio of F material, zirconia grinding beads, and deionized water is 1:2:0.8. The diameter of the zirconia grinding beads is 7mm, the grinding speed is 200rpm, and the grinding time is 9h. Step 1.4: The Ba2YNbO after the first ball milling treatment... 5.5 Material F was placed in an oven for drying at a temperature of 135℃ for 5 hours. Step 1.5: Dry the Ba2YNbO 5.5 Material F was placed in a crucible container in a sintering furnace and subjected to a second sintering process according to the following sintering regime: ammonia gas was introduced at a flow rate of 25 mL / min, the temperature was increased from room temperature to 1000℃ at a heating rate of 1.5℃ / min, held at the temperature for 45 h, and cooled to room temperature with the furnace to obtain Ba2(YNb)O4NF material. Step 1.6: Place the Ba2(YNb)O4NF material into a ball mill jar, and add deionized water and zirconia grinding beads. Perform a second ball milling treatment at room temperature, including the following main ball milling process parameters: mass ratio of Ba2(YNb)O4NF material, zirconia grinding beads, and deionized water 1:1.3:0.8, diameter of zirconia grinding beads 4mm, ball milling speed 200rpm, and ball milling time 9h; Step 1.7: Place the Ba2(YNb)O4NF material after the second ball milling treatment into an oven for drying at 135℃ for 5 hours.
[0051] The preparation method of the Ba2(YNb)O4NF material crucible includes the following main process parameters: The crucible blank is obtained by pressing at room temperature using a cold isostatic pressing equipment at a pressing pressure of 125 MPa and a holding time of 7.5 min; the crucible blank is then placed in a sintering furnace and sintered under a nitrogen atmosphere according to the following sintering regime: the temperature is increased from room temperature to 300℃ at a heating rate of 2℃ / min, held for 3 h, then increased to 1000℃ at a heating rate of 4℃ / min, held for 5.5 h, then increased to 1615℃ at a heating rate of 2℃ / min, held for 10 h, and then cooled to room temperature in the furnace to obtain the Ba2(YNb)O4NF material crucible.
[0052] In step four, the titanium and iron metals glow red and reach a preset temperature of 900°C, with a holding time of 5.5 minutes; the temperature continues to rise until the metals are completely melted, with a melting temperature of 1655°C; the refining temperature is 1775°C, and the refining time is 5.5 minutes.
[0053] The microstructure, elemental distribution, mechanical properties, and corrosion resistance of the above embodiments were tested under the same conditions and equipment. The macroscopic morphology of the Ti-Fe-ON alloy ingot prepared in Example 1 is as follows: Figure 1 As shown, the morphology of the backscattered electrons is as follows Figure 2 As shown, the element distribution is as follows Figure 3 As shown, Figure 2 The results show that the Ti-Fe-ON alloy is an α+β type alloy. Figure 3 The data shows that the elements are evenly distributed and there is no segregation.
[0054] A comparison of the corrosion resistance of the Ti-Fe-ON alloy ingots prepared in the four examples with that of the existing Ti-6Al-4V alloy ingots. Figure 4 As shown in the figure, the Ti-Fe-ON alloy ingot exhibits superior corrosion resistance.
[0055] The room temperature mechanical properties of the Ti-Fe-ON alloy ingots prepared in the four examples and the Ti-6Al-4V alloy ingots of the prior art are shown in Table 1.
[0056]
[0057] From Table 1 and Figure 4 As can be seen, through the synergistic design of alloy composition and preparation process, the prepared Ti-Fe-ON alloy can achieve excellent comprehensive mechanical properties, corrosion resistance and formability while ensuring low cost, and can effectively replace commercial Ti-6Al-4V alloy.
[0058] Special Note: The technical solution of this invention involves numerous parameters, and the synergistic effects between these parameters must be comprehensively considered to achieve the beneficial effects and significant progress of this invention. Furthermore, the value ranges of each parameter in the technical solution were obtained through extensive experimentation. For each parameter and the combinations thereof, the inventors have recorded a large amount of experimental data; however, due to space limitations, the specific experimental data is not disclosed here.
[0059] It will be readily understood by those skilled in the art that this invention includes any combination of the inventive description and specific embodiments outlined in the foregoing specification, as well as the various parts shown in the accompanying drawings. Due to space limitations and for the sake of brevity, not all of these combinations have been described in detail. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of this invention should be included within the scope of protection of this invention.
Claims
1. A high-performance, low-cost Ti-Fe-ON alloy, characterized in that, The mass percentage of each element in the Ti-Fe-ON alloy is as follows: 5wt% < Fe ≤ 8wt%, 0.2wt% ≤ O + N ≤ 0.5wt%, the mass ratio of N to O is 1:4-6, and the balance is Ti; the Fe content is negatively correlated with the sum of N + O content. Within the range of the sum of Fe content and N + O content, for every 1wt% increase in Fe addition, the N + O addition decreases by 0.08-0.1wt%.
2. A method for preparing a high-performance, low-cost Ti-Fe-ON alloy according to claim 1, characterized in that, The preparation method includes the following steps in sequence: Step 1: Prepare a crucible for Ba2(YNb)O4NF material according to the preset material ratio and process system; Step 2: Place the crucible in a vacuum induction melting furnace, and simultaneously put metallic titanium and metallic iron into the crucible; Step 3: Turn off the vacuum induction melting furnace and evacuate the furnace cavity to the preset vacuum level. While maintaining the preset vacuum level, gradually increase the power to induction heat the titanium and iron metals. Step 4: During the heating process of titanium and iron, high-purity argon gas is introduced for protection. After the titanium and iron turn red and reach the preset temperature, the temperature is held for a preset time, and then the temperature is continued to rise until the metal is completely melted. After the metal is completely melted, it is refined according to the preset refining temperature and refining time. After refining, the alloy melt is cast into an ingot to obtain a high-performance, low-cost Ti-Fe-ON alloy.
3. The method for preparing high-performance, low-cost Ti-Fe-ON alloy according to claim 2, characterized in that, In step one, the raw materials for preparing the Ba2(YNb)O4NF material crucible include barium carbonate, barium fluoride, yttrium oxide, niobium oxide, and ammonia. The mass ratio of barium carbonate, barium fluoride, yttrium oxide, and niobium oxide is 1:1.2-1.6:0.5:0.5, and the mass ratio of the sum of the masses of barium carbonate, barium fluoride, yttrium oxide, and niobium oxide to the mass of ammonia is 1:0.2-1.
3. The particle size of barium carbonate, barium fluoride, yttrium oxide, and niobium oxide is controlled within the range of 50-100 μm.
4. The method for preparing high-performance, low-cost Ti-Fe-ON alloy according to claim 3, characterized in that, In step one, the preparation method of the Ba2(YNb)O4NF material includes the following steps in sequence: Step 1.1: Place barium carbonate, barium fluoride, yttrium oxide and niobium oxide into a mixer and mix them evenly at room temperature. The mixing speed is 500-800 rpm and the mixing time is 30-60 min to obtain a dry powder mixture. Step 1.2: Place the dry powder mixture into a ceramic container, then place the ceramic container in a sintering furnace and perform the first sintering treatment under atmospheric atmosphere according to the following sintering regime: raise the temperature from room temperature to 200℃ at a heating rate of 0.8-1.5℃ / min, hold for 1-1.5h, continue to raise the temperature to 800℃ at a heating rate of 1.5-2℃ / min, hold for 2-4h, continue to raise the temperature to 1300℃ at a heating rate of 3-4℃ / min, hold for 10-20h, and cool to room temperature with the furnace to obtain Ba2YNbO. 5.5 F material; Step 1.3: Add Ba2YNbO 5.5 Material F was placed in a ball mill jar, along with deionized water and zirconia grinding beads. The first ball milling treatment was performed at room temperature, including the following main ball milling process parameters: Ba₂YNbO 5.5 The mass ratio of F material, zirconia grinding beads, and deionized water is 1:1.8-2.2:0.6-1. The diameter of the zirconia grinding beads is 6-8 mm, the grinding speed is 180-220 rpm, and the grinding time is 6-12 h. Step 1.4: The Ba2YNbO after the first ball milling treatment... 5.5 Material F is placed in an oven for drying at a temperature of 120-150℃ for 4-6 hours. During this drying process, Ba₂YNbO₂... 5.5 The particle size of material F is controlled within the range of 30-40 μm; Step 1.5: Dry the Ba2YNbO 5.5 Material F is placed in a ceramic container, and then the ceramic container is placed in a sintering furnace for a second sintering treatment according to the following sintering regime: ammonia gas is introduced at a flow rate of 20-30 mL / min, the temperature is raised from room temperature to 1000℃ at a heating rate of 1.2-1.8℃ / min, held at the temperature for 40-50 h, and then cooled to room temperature with the furnace to obtain Ba2(YNb)O4NF material. Step 1.6: Place the Ba2(YNb)O4NF material into a ball mill jar, and add deionized water and zirconia grinding beads. Perform a second ball milling treatment at room temperature, including the following main ball milling process parameters: the mass ratio of Ba2(YNb)O4NF material, zirconia grinding beads, and deionized water is 1:1.2-1.5:0.6-1, the diameter of the zirconia grinding beads is 3-5mm, the ball milling speed is 180-220rpm, and the ball milling time is 6-12h. Step 1.7: Place the Ba2(YNb)O4NF material after the second ball milling treatment into an oven for drying. The drying temperature is 120-150℃ and the drying time is 4-6h. At this time, the particle size of the Ba2(YNb)O4NF material is controlled within the range of 10-20μm.
5. The method for preparing high-performance, low-cost Ti-Fe-ON alloy according to claim 4, characterized in that, In step one, the preparation method of the Ba2(YNb)O4NF material crucible includes the following steps in sequence: First, pour the dried Ba2(YNb)O4NF material into a U-shaped crucible mold; Then, the crucible blank is formed by pressing at room temperature using a cold isostatic pressing equipment with a pressing pressure of 100-150MPa and a holding time of 5-10min. Finally, the crucible blank is placed in a sintering furnace and sintered under a nitrogen atmosphere according to the following sintering regime: the temperature is increased from room temperature to 300℃ at a heating rate of 1-3℃ / min, held for 2-4 hours, then increased to 1000℃ at a heating rate of 3-5℃ / min, held for 5-6 hours, then increased to 1580-1650℃ at a heating rate of 1-3℃ / min, held for 8-12 hours, and then cooled to room temperature with the furnace to obtain the Ba2(YNb)O4NF material crucible.
6. The method for preparing high-performance, low-cost Ti-Fe-ON alloy according to claim 5, characterized in that, In step two, the titanium metal is added in any of the following forms: sponge titanium, titanium metal blocks, or titanium powder; and the iron metal is added in any of the following forms: iron powder, iron granules, or iron blocks.
7. The method for preparing high-performance, low-cost Ti-Fe-ON alloy according to claim 6, characterized in that, In step three, the furnace cavity is evacuated to a vacuum level of 1×10⁻⁶. -3 ~1×10 -2 Pa.
8. The method for preparing high-performance, low-cost Ti-Fe-ON alloy according to claim 7, characterized in that, In step four, the titanium and iron metals glow red and reach a preset temperature of 600-1200℃, and the holding time is 1-10 minutes.
9. The method for preparing high-performance, low-cost Ti-Fe-ON alloy according to claim 8, characterized in that, In step four, the temperature is increased until the metal is completely melted, at a melting temperature of 1630-1680℃.
10. The method for preparing high-performance, low-cost Ti-Fe-ON alloy according to claim 9, characterized in that, In step four, the refining temperature is 1700-1850℃ and the refining time is 1-10 minutes; the casting mold includes any one of metal shell, graphite shell and ceramic shell.